Prefoldin 5 and Anti-prefoldin 5 Antibodies as Biomarkers for Uveitis in Ankylosing Spondylitis - Kwon, Oh Chan; Lee, Eun-Ju; Lee, Joo Yong; Youn, Jeehee; Kim, Tae-Hwan; Hong, Seokchan; Lee, Chang-Keun; Yoo, Bin; Robinson, William H.; Kim, Yong-Gil (Frontiers in Immunology, 2019)
Objective: Uveitis is the most common extra-articular manifestation of ankylosing spondylitis (AS), for which no diagnostic biomarkers have been identified. This study was conducted to identify biomarker for uveitis in AS. Methods: To identify autoantibodies associated with uveitis in AS, we performed human protein microarray analysis using sera derived from various autoimmune diseases and ELISA analysis of sera derived from AS and rheumatoid arthritis patients. In the curdlan-induced SKG mice model, ophthalmic examination was performed at week 8 post-immunization and histologic examination of the ocular lesions performed at week 16 post-immunization. Serum levels of target antibodies were assessed at various time-points. To evaluate the functional role of specific autoantibodies, an in vitro apoptosis assay using ARPE-19 cells was performed. Results: Reactivity against prefoldin subunit 5 (PFDN5) was identified in AS with uveitis. Levels of anti-PFDN5 antibodies and PFDN5 in sera from AS with uveitis patients were significantly higher than those in AS without uveitis. At week 8, half of curdlan-treated SKG mice developed anterior uveitis, while all of them developed histologically confirmed uveitis at week 16. The levels of anti-PFDN5 antibodies increased over time in the sera of curdlan-treated SKG mice along with increased expression of PFDN5 and apoptosis in the ocular lesions. Knockdown of PFDN5 in ARPE19 cells resulted in increased apoptosis, suggesting a protective role of PFDN5 against cell death in uveitis. Conclusion: AS patients with uveitis have increased levels of anti-PFDN5 antibodies, and our findings suggest that anti-PFDN5 antibodies could provide a biomarker for uveitis in AS.